2013
DOI: 10.4111/kju.2013.54.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Failure of Early Catheter Removal After Greenlight HPS Laser Photoselective Vaporization Prostatectomy in Men With Benign Prostatic Hyperplasia

Abstract: PurposeTo assess the risk factors for developing urinary retention after removal of the urethral catheter on postoperative day 1 in benign prostatic hyperplasia patients who underwent Greenlight HPS laser photoselective vaporization prostatectomy (PVP).Materials and MethodsThe study included 427 men who underwent Greenlight HPS laser PVP between 2009 and 2012, excluding patients in whom a catheter was maintained for more than 1 day because of urethral procedures. In all patients, a voiding trial was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The mean IPSS was 34.69 ± 1.34 with a p-value of 0.710. Comparing with the study of Bae WJ et al, their mean IPSS was 21.45 ± 0.54 23 ; it is believed that severe IPSS was because of the severe dysuria felt by the patient in their earlier voids. Despite an improved caliber of urinary stream the patient felt hesitant to void post early catheter removal.…”
Section: 17%mentioning
confidence: 51%
“…The mean IPSS was 34.69 ± 1.34 with a p-value of 0.710. Comparing with the study of Bae WJ et al, their mean IPSS was 21.45 ± 0.54 23 ; it is believed that severe IPSS was because of the severe dysuria felt by the patient in their earlier voids. Despite an improved caliber of urinary stream the patient felt hesitant to void post early catheter removal.…”
Section: 17%mentioning
confidence: 51%
“…; P = 0.012]; however, the anxiety level before PVP surgery was not signi cantly different between the groups (3 [3][4] vs. 3 [3][4], P = 0.140]. In addition, urinalysis revealed that the WBC count in the perfusion group was signi cantly lower than that in the control group on the day [25.5(8-37.75) vs. 43.5(24.0-64.75); P < 0.001] and 2 weeks [20.5 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) vs 31.0(20-42); P < 0.001] after catheter removal (Table 4). All postoperative complications that occurred during the 6-month follow-up period are summarized in Table 5.…”
Section: Resultsmentioning
confidence: 97%
“…Although surgical clinical outcomes of PVP have been con rmed worldwide, the time of catheter removal after PVP is inconclusive [12], and saline perfusion before catheter removal has not yet been reported. Patients treated with PVP usually require catheterization for 1-9 days, which is determined by the patient and PVP surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Bae et al [13] conducted a consecutive cohort study with a total of 427 patients treated with HPS and tried to determine the risk factors responsible…”
Section: Greenlight Laser Vaporizationmentioning
confidence: 99%